Development of an Amperometric Glucose Biosensor Based on the Immobilization of Glucose Oxidase on the Se-MCM-41 Mesoporous Composite. (10th May 2018) - Yusan, Sabriye; Rahman, Mokhlesur M.; Mohamad, Nasir; Arrif, Tengku M.; Latif, Ahmad Zubaidi A.; M. A., Mohd Aznan; Wan Nik, Wan Sani B.
Abstract : A new bioenzymatic glucose biosensor for selective and sensitive detection of glucose was developed by the immobilization of glucose oxidase (GOD) onto selenium nanoparticle-mesoporous silica composite (MCM-41) matrix and then prepared as a carbon paste electrode (CPE). Cyclic voltammetry was employed to probe the catalytic behavior of the biosensor. A linear calibration plot is obtained over a wide concentration range of glucose from 1 × 10 −5 to 2 × 10 −3  M. Under optimal conditions, the biosensor exhibits high sensitivity (0.34  µ A·mM −1 ), low detection limit (1 × 10 −4  M), high affinity to glucose (Km  = 0.02 mM), and also good reproducibility (R.S.D. 2.8%, n = 10 ) and a stability of about ten days when stored dry at +4°C. Besides, the effects of pH value, scan rate, mediator effects on the glucose current, and electroactive interference of the biosensor were also discussed. As a result, the biosensor exhibited an excellent electrocatalytic response to glucose as well as unique stability and reproducibility.